PENGEMBANGAN (LKPD) DENGAN PENDEKATAN (STEM) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Zebua, Siska Yanti; Mendrofa, Ratna Natalia; Telaumbanua, Yakin Niat; Zega, Yulisman (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to develop a Learner Worksheet (LKPD) with Science, Technology, Engineering and Mathematics (STEM) approach to improve students' mathematical problem-solving ability that is valid, practical, and effective. Students' mathematical problem-solving ability that is valid, practical, and effective. This research is development research (Research and Development) with the ADDIE development model which consists of 5 stages of development, namely analysis, Design stages, namely analysis, design, development, implementation, and evaluation. The results showed that the LKPD with the STEM approach on the material “quadrilateral and triangle” has met the criteria of valid, effective, and effective. and triangle” have met the criteria of valid, practical, and effective. The validity results validity results obtained from material experts, linguists, and design experts obtained an average of 74.95%, while the practical results obtained were average of 74.95%, while the practical results of students obtained an average of 90.61%, and practical practical results of 90.61%, and the effectiveness test results obtained an average of 72,97. It can be concluded that the LKPD with the STEM approach is categorized as very valid, very practical, and very effective for improving students' mathematical problem solving skills. Students' mathematical problem-solving ability.